Entornos virtuales como herramientas en el aprendizaje de los estudiantes de la Carrera de Pedagogía de la Actividad Física y Deporte periodo 2022 - Valero Moreno, Katherine Jamilex (2022)
Currently, the implementation of technological resources in the educational system has transformed the teaching-learning methodology, facilitating communication between teachers and students. Therefore, the purpose of this study is to identify the virtual learning environments in the pedagogical process in the Pedagogy of Physical Activity and Sports career at the Technical University of Babahoyo. The research is quantitative in nature with an exploratory and descriptive scope, likewise documentary research was used consisting of the review of bibliographic materials, which allowed describing the use, importance and benefits offered by virtual learning environments and the survey technique. that allowed the collection, analysis and interpretation of compiled data. Finally, the results obtained have shown that EVAs as tools in the learning process have contributed significantly as means of interaction, promoting collaborative, competitive and innovative work.